Covid-19 and inequality: developing an age-friendly strategy for recovery in low income communities. (2nd December 2020) - Buffel, Tine; Doran, Patty; Goff, Mhorag; Lang, Luciana; Lewis, Camilla; Phillipson, Chris; Yarker, Sophie
Abstract : Purpose: This paper aims to explore the social impact of the COVID-19 pandemic, focusing on issues facing older people living in urban areas characterised by multiple deprivation. Design/methodology/approach: The paper first reviews the role of place and neighbourhood in later life; second, it examines the relationship between neighbourhood deprivation and the impact of COVID-19; and, third, it outlines the basis for an "age-friendly" recovery strategy. Findings: The paper argues that COVID-19 is having a disproportionate impact on low-income communities, which have already been affected by cuts to public services, the loss of social infrastructure and pressures on the voluntary sector. It highlights the need for community-based interventions to be developed as an essential part of future policies designed to tackle the effects of COVID-19. Originality/value: The paper contributes to debates about developing COVID-19 recovery strategies in the context of growing inequalities affecting urban neighbourhoods.